FAMILY SOCIALISATION FUNCTION IN OUT-OF-SCHOOL CHILDREN - Nikita Khoerunnisa; Nurhadi Nurhadi; Dwi Astutik (Al-Amien Prenduan University, Sumenep, 2023)
The Wonosobo District Government has endeavored to tackle the problem of out-of-school children through the